S-allyl-L-cysteine and isoliquiritigenin improve mitochondrial function in cellular models of oxidative and nitrosative stress - Denzer, Isabel; Münch, Gerald; Pischetsrieder, Monika; Friedland, Kristina (Food Chemistry, 2016)
Oxidative and nitrosative stress resulting in mitochondria( dysfunction are an early event in the pathogenesis of Alzheimer's disease (AD). Nuclear factor erythroid-2-related factor 2 (Nrf2) is a key transcription factor and regulator of the cellular response to oxidative stress. Thus known Nrf2 activators from food materials were tested for improvement of mitochondrial membrane potential (MMP) and ATP level in neuronal pheochromocytoma cell (PC12) models of oxidative and nitrosative stress. The effects of rotenone and sodium nitroprusside (complex inhibitors of the respiratory chain) on mitochondrial function were also studied. Furthermore, Nrf2 activators were tested in human embryonic kidney cells bearing the Swedish mutation of amyloid precursor protein (APP(sw) HEK cells) as a cellular model of familial AD. Preincubation with S-allyl-L-cysteine and isoliquiritigenin increased MMP in both PC12 cell models in a similar range as the positive control L-sulforaphane. None of the test compounds, however, improved MMP and ATP level in APP(sw) HEK cells. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Mitochondrial dysfunction; Oxidative stress; Nrf2; Alzheimer's disease; Aging